Comparison of the linear bias models in the light of the Dark Energy Survey. Issue 2 (16th February 2018) - Papageorgiou, A; Basilakos, S; Plionis, M
Abstract: The evolution of the linear and scale independent bias, based on the most popular dark matter bias models within the Λ cold dark matter (ΛCDM) cosmology, is confronted to that of the Dark Energy Survey (DES) luminous red galaxies (LRGs). Applying a χ 2 minimization procedure between models and data, we find that all the considered linear bias models reproduce well the LRG bias data. The differences among the bias models are absorbed in the predicted mass of the dark-matter halo in which LRGs live and which ranges between ∼6 × 10 12 and 1.4 × 10 13   h −1  M⊙, for the different bias models. Similar results, reaching however a maximum value of ∼2 × 10 13   h −1  M⊙, are found by confronting the SDSS (2SLAQ) Large Red Galaxies clustering with theoretical clustering models, which also include the evolution of bias. This later analysis also provides a value of Ωm  = 0.30 ± 0.01, which is in excellent agreement with recent joint analyses of different cosmological probes and the reanalysis of the Planck data.